Musical and non-musical experiences of undergraduate music students’ mobility programme in South Korea between 2014 - 2016 / Lim Jia Yin - Lim , Jia Yin (2020)
Nowadays, trend of international student mobility is increasing. Due by the growth of globalization international high education has been developing. There are many education institutions promote and offer the program of study abroad. This development has led to an increase of higher education research. There are substantial researchers are aiming to understand the influences, motivation, and benefits of study abroad. However, due to the increasing complexity of mobility, getting popular in contemporary period, there seem to be contradictions within their empirical data. By studying for a short term in Korea, students are able to experience studying abroad through the lens of academic, musical, cultural, and lifestyle. This study aims to gain an insight of the international study mobility; to present the influences factors of international student mobility; to contribute to the scholastic resources for a deeper understanding of international student mobility; and to discover the achievements of the international student mobility.